Nanotechnology - Gregory L Timp (AIP Press : Springer, 1999)
This volume is a survey of the machinery and science of the nanometer scale. Its twenty-two contributing authors, drawn from many different disciplines including atomic physics, microelectronics, polymer chemistry, and bio-physics, delineate the course of current research and articulate a vision for the development of the nanometer frontiers in electronics, mechanics, chemistry, magnetics, materials, and biology.